Pengaruh Limbah Padi dan Pupuk Kandang Terhadap Pertumbuhan Bibit Tembakau Virginia (Nicotiana tabacum L.) - Hariyono, Hariyono (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2016)
The experiment entitled the effect of using composisition rice residues and animal manure for media utilization on growth seedling of Virginia tobacco (Nicotiana tabacum L.) in seedbad was conducted to determine the approriate kind of rice residues and animal manure for seedbad for Virginia tobacco. The experiment was conducted at Pakis, Delanggu. The factorial experiment was arranged in the Complete Randomized Design with 12 combinations of treatment. The first factor was kinds of rice residues consisted : rice Straw, rice chaff, and rice bran. The second factor was kinds of animal manure consisted of manure of cow, manure of goat, and manure of chicken. The results of experiment showed that combination of rice straw and manure of chicken is the best treatment for seedling the Tobacco Virginia.